2014
DOI: 10.1002/rnj.92
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Brief Self-Care Support Intervention for Pulmonary Rehabilitation Among the Elderly Patients with Chronic Obstructive Pulmonary Disease in Korea

Abstract: Our findings suggest a brief intervention for rehabilitation nursing with more retainable, feasible, and cost-effective strategies to enhance self-management among the elderly patients with COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(74 citation statements)
references
References 33 publications
0
71
0
Order By: Relevance
“…, Song et al . ). Besides, not all of these reviews are aimed at interventions specifically conducted by nurses (Bentsen et al .…”
Section: Introductionmentioning
confidence: 97%
“…, Song et al . ). Besides, not all of these reviews are aimed at interventions specifically conducted by nurses (Bentsen et al .…”
Section: Introductionmentioning
confidence: 97%
“…Four studies (Boxall et al, ; Pradella et al, ; Song et al, ; Xu & Liu, ) involving 197 elderly patients showed changes in Borg scores when using the pulmonary rehabilitation. The meta‐analysis found that pulmonary rehabilitation significantly improved Borg scores compared with routine therapy alone.…”
Section: Resultsmentioning
confidence: 99%
“…After downloading to Endnote Version 7 and elimination of duplicate records, the remaining 406 articles were screened by titles and abstracts. After screening 84 articles for full‐text reading and after excluding articles that were inconsistent with outcome measures and therapeutic goals, eight studies involving 414 patients met the inclusion criteria (Boxall, Barclay, Sayers, & Caplan, ; Hao, Sun, Zhao, Liu, & Zheng, ; Karapolat et al, ; Pradella et al, ; Song, Yong, & Hur, ; Wedzicha et al, ; Xu & Liu, ; Zhong, Lin, Zhang, & Zhou, ) and, with quality assessment, were included in this review.…”
Section: Review Methodsmentioning
confidence: 99%
“…Six studies evaluated nursing interventions performed in clinics with home follow‐up. The studies were conducted in the Netherlands (Bischoff et al., ), Taiwan (Kuo et al., ), Korea (Song, Yong, & Hur, ), England (Sridhar, Taylor, Dawson, Roberts, & Partridge, ) and China (Wang et al., ; Yu, Guo, & Zhang, ) and included a total sample of 473 participants. The main content of the interventions was self‐management education about living with COPD, COPD management, management of exacerbations, motivational interviewing and pulmonary rehabilitation.…”
Section: Resultsmentioning
confidence: 99%